1993
DOI: 10.1177/000331979304401010
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Gangrenous Lesions in the Blue Toe Syndrome with Lovastatin A Case Report

Abstract: A seventy-six-year-old man with ischemic heart disease, peripheral vascular disease, and chronic renal failure developed bilateral cyanotic toes, which upon muscle biopsy, were shown to be caused by atheromatous emboli. The probable source was atheromatosis of the abdominal aorta. The toes became gangrenous, but surgical therapy was deferred because the patient was considered a high risk. With lovastatin therapy there was complete healing and except for transient cyanosis related to temporary cessation of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…To date, the role of statins in AERD remains uncertain, because only occasional cases have responded to lovastatin and simvastatin (11,12). Because deterioration in renal function over several weeks observed in the majority of patients with AERD suggests an ongoing embolic process, strategies should be developed to stabilize ulcerated atherosclerotic plaques showering cholesterol emboli into renal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of statins in AERD remains uncertain, because only occasional cases have responded to lovastatin and simvastatin (11,12). Because deterioration in renal function over several weeks observed in the majority of patients with AERD suggests an ongoing embolic process, strategies should be developed to stabilize ulcerated atherosclerotic plaques showering cholesterol emboli into renal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que estabilizam as placas de colesterol, mas não há uma indicação absoluta no tratamento desta condição 23 24 . O fato da deterioração da função renal se dar por semanas, como observado na maioria dos pacientes com DRAE, sugere a presença de um processo embólico contínuo.…”
Section: Discussionunclassified
“…Specific treatments remain to be established, with the prognosis being poor. 1 Cholesterol-lowering drugs 22 and glucocorticoids 23,24 have been reported to be effective in improving the clinical symptoms of CCE, although there is disagreement regarding these treatments. Hasegawa et al 25 reported that combined therapy with steroid and plasma exchange was effective in patients with renal failure and CCE, while Belenfant et al 26 demonstrated that aggressive supportive treatment incorporating control of hypertension and heart failure, dialytic therapy, and adequate nutrition was associated with a significant improvement in survival rate.…”
Section: Discussionmentioning
confidence: 99%